A study on Vulvovaginal candidiasis among non-pregnant women - Dr. Kavitha.Y; Dr. Mohan S; Dr. Anandi V; Dr. Harish Babu (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Candida species are opportunistic pathogens which cause a wide variety of infections in humans ranging from trivial intertriginous infection to fatal candidemia. Vulvo vaginal candidiasis (VVC) is an acute inﬂammatory disease and a frequent reason for gynaecological consultations. The present study aimed at determining prevalence of Candida species from VVC and to speciate isolated Candida with antifungal susceptibility profile among non pregnant women.Materials and Methods: This was a cross sectional study conducted over a period of six monthsin the department of microbiology and Obstetrics and Gynecology. Swabs collected from patients were subjected to microscopy (Gram s stain) and culture on Sabouraud’s dextrose agar. Species level was identified by using chrome agar. Antifungal susceptibilitytesting: Antifungal susceptibility testing was performed by NCCLS M44 -A Disc diffusion method.Results: A total of 209 high vaginal swabs were collected from non pregnant women. 71 patients high vaginal swabs yielded growth of Candida species and accounted for 33.97%. Most commonly isolated species were Candida albicans 31 (43.66%) followed by Candida tropicalis 27(38.03%) and Candida glabrata 13(18.31%). All species were found to be susceptible to Amphotericin B. Among commonly used antifungals, clotrimazole was found to be most susceptible. But, C.glabrata species was least susceptible to frequently used antifungals.Conclusion: Candida albicans was the most commonly isolated species.CHROMagar is rapid, technically simple and cost effective compared to time consuming technically demanding expensive conventional methods. Performing antifungal susceptibility is useful in choosing appropriate antifungal in treating vulvo vaginal candidiasis.